Association study of the beta-adrenergic receptor genetic variant Gly389Arg and fluoxetine response in major depression: - Firouzabadi, Negar; Asadpour, Roja; Zomorrodian, Kamiar (Galen Medical Journal, 2020)
Background: Pharmacogenetics has proven role in the treatment of different illnesses. Patients with special genotypes may achieve a better response to a specific drug. On the other hand, genetic parameters markedly contribute to the development of major depressive disorder (MDD). The significance of adrenergic system compartments in cognition and behavior, and their role in etiology of depression denote that adrenergic receptors beta gene polymorphism(s) might also have an association with drug response. Thus this study aims to evaluate the association between β1AR gene polymorphisms, G1165C, Arg389Gly and response to fluoxetine in MDD patients. Materials and Methods: Among different antidepressants, we focused on fluoxetine as it is prescribed frequently in MDD and belongs to one of the most efficient antidepressant categories with minimum side effects. MDD was diagnosed at study entry using DSM-IV criteria. One hundred and one new MDD patients were treated with fluoxetine for a period of 6 weeks. A 50% decrease in Hamilton Rating Scale for Depression (HRSD) was considered as response to treatment. Genotyping of G1165C polymorphism was performed by PCR-RFLP method. Results: Results of the study indicated no significant relationship between β1AR polymorphism and the patient’s response to fluoxetine neither at genotypic nor allelic level (P=0.568). Conclusion: Our study did not support the hypothesis of involvement of β1AR Arg389Gly polymorphism and response to fluoxetine in MDD patients. [GMJ.2020;9:e1781]